Wulf and Eadwacer, eddic verse, and aural aesthetics. Issue 1 (21st April 2021) - Rozano-García, Francisco J.
Abstract: This study reexamines the case for Old Norse influence on the Old English poem Wulf and Eadwacer by considering the potential adaptation of Old Norse metrical grammar to the conventions of Old English verse, which results in the poem's unusual structure, syntax, and diction. The case for Old Norse influence on the poem is reconsidered here in the light of recent studies of the imitative technique of the Old English poet, which hints at conscious adaptation of external traditions to the conventions of Old English verse, rather than at direct translation of an Old Norse source. Reappraisal of the possibilities of interpretation derived from hybrid composition technique reveals that the Wulf and Eadwacer poet worked within an adaptative process that accommodates Old English and Old Norse semantic possibilities while maintaining an aural esthetics that consciously imitates eddic verse.